Digital Teaching Material of Integrated Science with Blended-PBL Model for Independent Curriculum - Fitria, Dinelti; Lufri; Asrizal; N, Annisa (Jurnal Penelitian Pendidikan IPA, 2024)
The Independent curriculum demands student-centered learning by utilizing technology, so that students' 21st century skills can develop. However, what is found at school is very contrary to the demands of learning in the independent curriculum. As a solution, Digital Integrated Science Teaching Materials Integrated Blended-PBL Model (DTMIS-Blended-PBL) was developed for the development of the Independent Curriculum. This research aims to determine the needs analysis, validity, and practicality of integrated digital science model teaching materials with PBL models. The research method used is the development method with the Ploomp. Research data in the form of knowledge scores, creative thinking skills, and communicative skills of students, validity and practicality of DTMIS-Blended-PBL. Based on the research results, three conclusions can be presented. First, there are problems in learning, especially low student achievement and creative and communicative thinking skills. Second, DTMIS-Blended PBL is valid with an average score of 0.87. Third, DTMIS-Blended PBL is practical with an average score of 93.53. Therefore, the developed DTMIS-Blended PBL is valid and practical so it has the potential to improve the quality of science learning and support the implementation of the Independent Curriculum.